223k views
2 votes
Help.................solve for y:7=-3/2 y

User Yomateo
by
4.3k points

1 Answer

4 votes

Given the equation:


7=-(3)/(2)y

notice that we can multiply both sides by 2 to get rid of the denominator on the right, then, we would have the following:'


\begin{gathered} (7=-(3)/(2)y)\cdot(2) \\ \Rightarrow2(7)=-(3)/(2)(2)y \\ \Rightarrow14=-3y \end{gathered}

then, we can move the -3 that is multiplying the variable y to the left side dividing:


\begin{gathered} 14=-3y \\ \Rightarrow(14)/(-3)=y \\ y=-(14)/(3) \end{gathered}

therefore, y = -14/3

User Baxterma
by
4.7k points